Meningkatkan Identitas Nasional Dan Persepsi Positif Siswa Terhadap Globalisasi melalui Creative Productive Learning [Increasing National Identity and Student's Positive Perception of Globalization Through Creative Productive Learning] - Agus Santoso; HG Retno Harsanti (Jurnal Teropong Pendidikan, 2022)
National culture and globalization are two inseparable things. Globalization plays a huge role in spreading and interacting with cultures in different parts of the world. On the one hand, there are positive aspects of globalization, such as the ease of access to information and global communication. On the other hand, globalization impacts the fading of national culture due to global interactions. This study aimed to analyze the application of creative productive learning (CPL) methods to increase the perception of national identity and students' positive perceptions of globalization. The research design in this study was classroom action research (CAR), which was conducted on 11th-grade students of SDH Daan Mogot, Jakarta, in three cycles. Data were collected through interviews, questionnaires, and documentation. This study indicates that the CPL method can increase the perceptions of national identity and students' positive perceptions of globalization.